2020
DOI: 10.3390/polym12102207
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flaxseed Oil Bimodal Emulsions Prepared with Flaxseed Oil Cake Extract Applied as a Natural Emulsifying Agent

Abstract: Currently, a majority of oilseeds plants are converted into byproducts and waste materials during processing. Press cakes are rich in valuable biopolymers, such as proteins and polysaccharides (fiber, lignans, etc.). In this study flaxseed oil cake extract (FOCE) was used to stabilize flaxseed oil-in-water emulsions. The effect of FOCE with various flaxseed oil concentrations (10–50% v/v) on several physicochemical properties of emulsions, such as stability, rheology, color and particle size was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 69 publications
(139 reference statements)
3
39
0
Order By: Relevance
“…The droplet size was essential for the stability of the emulsion, as emulsions with a controlled particle size exhibited greater stability. Moreover, it was suggested that the smaller the droplets, the higher was the emulsion stability [5]. In fact, the lowest D 4,3 (2.693 ± 0.00 µm) and D 3,2 (2.166 ± 0.01 µm) after reconstitution were observed for the sample FOCE-MS-20%.…”
Section: Emulsion Characteristics 321 Emulsion Particles Size Changesmentioning
confidence: 98%
See 4 more Smart Citations
“…The droplet size was essential for the stability of the emulsion, as emulsions with a controlled particle size exhibited greater stability. Moreover, it was suggested that the smaller the droplets, the higher was the emulsion stability [5]. In fact, the lowest D 4,3 (2.693 ± 0.00 µm) and D 3,2 (2.166 ± 0.01 µm) after reconstitution were observed for the sample FOCE-MS-20%.…”
Section: Emulsion Characteristics 321 Emulsion Particles Size Changesmentioning
confidence: 98%
“…This might be an explanation for the decreased yield in this study, which is observed for samples with FOCE. The dry matter content of FOCE was reported at approximately 3% and consists of flaxseed proteins, polysaccharides (flaxseed gum), and another extractable compounds [5]. In the presented study, FOCE was used as a liquid phase and its components played the role of emulsifying agents, but should also be calculated for the total solids concentration.…”
Section: Powders Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations